The effect of Health Education using Audio Visual Media on knowledge about the impact of young marriage on adolescents in SMK Islam Qiyamu at-Tarbiyah Batukliang subdistrict - Jihadi, Lalu Helmi; Wiresenta, Lalu; Fitria Frisma Lita; Fitrihan Rukmana (Mataram University, 2024)
Young marriage is a marriage that occurs among teenagers aged under 20 years. The Central Statistics Agency (BPS) 2022 stated that in the last 4 years from January 2019 to April 2022, there were at least 2,530 cases of young marriages that occurred in various regions in West Nusa Tenggara Province. This research aims to determine the effect of health education using audio-visual media on knowledge about the impact of early marriage on teenage children at Qiyamu At-Tarbiyah Islamic Vocational School, Batukliang sub-district 2023. The research method is quasi-experimental research with a one-group serial design. The population in this study were all students at Qiyamu At-Tabiyah Islamic Vocational School, Batukliang District. The total sample was 52 people, and the sampling method used was non-probability. There is a statistical difference in the results of an increase in knowledge between before and after being given health education with a significant value of 0.000 < 0.001. This research concludes that health education is effective in increasing students' knowledge about the impact of young marriage at Qiyamu At-Tarbiyah Islamic Vocational School.